“Are You Ready?” Revisiting Needs Analysis for ESP Online Conversation Course - Rahmawati, Noni Mia (IJET (Indonesian Journal of English Teaching), 2021)
It is common to be found in an ESP class where the students are not fully engaged in the learning activities due to their lack of interests toward English. To attract the ESP students’ interests, authentic materials and meaningful activities need to be provided. Online learning can bring authentic materials to ESP students and give them meaningful activities as they can interact with native speakers of English through many online platforms. To fit the students’ online learning situations to their learning experiences, as well as the materials and activities to be given, a needs analysis should be carried out. The study focuses on discovering the ESP students’ preparedness in performing an online English conversation course by conducting a needs analysis. Questionnaires were given to 82 students and an interview was performed with 17 students to gain the data. The data collected in the form of percentages were analyzed by describing them qualitatively. From the analysis, it can be concluded that the ESP students were prepared to join the online English conversation course.